2023
DOI: 10.3390/molecules28083436
|View full text |Cite
|
Sign up to set email alerts
|

Altered Glycosylation in Progression and Management of Bladder Cancer

Abstract: Bladder cancer (BC) is the 10th most common malignancy worldwide, with an estimated 573,000 new cases and 213,000 deaths in 2020. Available therapeutic approaches are still unable to reduce the incidence of BC metastasis and the high mortality rates of BC patients. Therefore, there is a need to deepen our understanding of the molecular mechanisms underlying BC progression to develop new diagnostic and therapeutic tools. One such mechanism is protein glycosylation. Numerous studies reported changes in glycan bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 216 publications
0
4
0
Order By: Relevance
“…RPN1 is a protein involved in the process of protein synthesis within cells and is responsible for N-glycosylation in the ER of cells [25]. Abnormal or altered N-glycosylation have been suggested to influence the signaling pathways involved in cell proliferation, migration, and angiogenesis in cancer progression [26,27]. Accumulating studies have reported that RPN2 is implicated in multiple cancers, such as breast cancer [28], small-cell lung cancer [29], bladder cancer [30], and colon carcinoma [31].…”
Section: Discussionmentioning
confidence: 99%
“…RPN1 is a protein involved in the process of protein synthesis within cells and is responsible for N-glycosylation in the ER of cells [25]. Abnormal or altered N-glycosylation have been suggested to influence the signaling pathways involved in cell proliferation, migration, and angiogenesis in cancer progression [26,27]. Accumulating studies have reported that RPN2 is implicated in multiple cancers, such as breast cancer [28], small-cell lung cancer [29], bladder cancer [30], and colon carcinoma [31].…”
Section: Discussionmentioning
confidence: 99%
“…The role of general glycosylation levels in the cellular proteome of bladder cancer cells specifically is becoming clearer with recent studies. It is evident that alterations to a number of glycan synthesis pathways are associated with bladder cancer occurrence, more advanced disease, and poor prognosis [ 30 ]. Another hallmark of abnormal glycan synthesis and protein modification in bladder cancer is the increased appearance of Tumor-Associated Carbohydrate Antigens (TACAs) [ 31 , 32 ].…”
Section: Glycosylation and Bladder Cancermentioning
confidence: 99%
“…Additional TACAs occur as a result of different saccharide molecules being added in an O-glycosylation-deficient environment, such as STn, T, and Lewis antigens. All of these abnormal antigens are considered significant biomarkers in bladder cancer, along with a host of other altered glycosylation events [ 30 ]. A very intriguing, recent development in assisting clinicians with choosing the best treatment for bladder cancer patients is the development of a glycosylation risk score [ 34 ].…”
Section: Glycosylation and Bladder Cancermentioning
confidence: 99%
“…Recently, immune checkpoint inhibitors (ICI) for BLCA patients were approved, showing modest 20–25% success rates in providing improved overall survival and progression free survival [ 1 , 3 , 4 ], urging novel therapeutic strategies. Advanced BLCA is characterized by alterations in glycosylation pathways, mainly oversialylation of terminal glycans and consequent arrest in proteins O -glycosylation [ 5 ]. This event is translated by the overexpression of sialylated short-chain O -GalNAc glycans, such as sialyl-Tn (STn) and mono/di sialylated T (ST) antigens [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%